Preferences, Perceptions, and Veto Players: Explaining Devolution Negotiation Outcomes in the Canadian Territorial North - Alcantara, Christopher (Scholars Commons @ Laurier, 2012)
Since the early part of the 20th century, the federal government has engaged in a long and slow process of devolution in the Canadian Arctic. Although the range of powers devolved to the territorial governments has been substantial over the years, the federal government still maintains control over the single most important jurisdiction in the region, territorial lands and resources, which it controls in two of the three territories, the Northwest Territories and Nunavut. This fact is significant for territorial governments because gaining jurisdiction over their lands and resources is seen as necessary for dramatically improving the lives of residents and governments in the Canadian north. Relying on archival materials, secondary sources, and 33 elite interviews, this paper uses a rational choice framework to explain why the Yukon territorial government was able to complete a final devolution agreement relating to lands and resources in 2001 and why the governments of the Northwest Territories and Nunavut have not. It finds that the nature and distance of federal-territorial preferences, combined with government perceptions of aboriginal consent and federal perceptions of territorial capacity and maturity, explain the divergent outcomes experienced by the three territorial governments in the Canadian arctic. The following acronyms are employed: AIP: Agreement-in-Principle; DTA: Devolution Transfer Agreement; GEB: gross expenditure base; GN: Government of Nunavut; GNWT: Government of Northwest Territories; NCLA: Nunavut Land Claims Agreement; NTI: Nunavut Tunngavik Incorporated; NWT; Northwest Territories; ON: Ontario; TFF: Territorial Formula Financing; UFA: Umbrella Final Agreement; YDTA: Yukon Devolution Transfer Agreement; YTG: Yukon Territorial Government; YK: Yukon;